There Can Be No Successful Logical Argument from Evil - Vecchio, Daniel (New blackfriars, 2025)
Brian Leftow’s observation that the logical problem of evil is largely resolved, mainly due to the success of free-will defenses, is not universally accepted.1 Graham Oppy, for instance, acknowledges the current shortcomings in formulating a logical argument from evil but contends that deeming such efforts futile is premature.2 Likewise, James Sterba’s recent work shows continued attempts to develop this argument.3 These views prompt a critical question: Is constructing a successful logical argument from evil futile, or will persistence yield success as it has in other philosophical inquiries?This article introduces the ‘Layers of Reality Response’ to the logical problem of evil, aiming to conclusively resolve the debate for classical theists, independent of free-will defenses. This response establishes two points:1. Common linking principles in logical arguments from evil are not evidently true and fail to apply across different layers of reality.2. There is no non-question-begging linking principle for proponents of the logical argument from evil, making a successful formulation inherently unachievable.If correct, this renders the logical argument from evil not just a philosophical failure but an argument that cannot, in principle, be successfully reformulated – it is not only dead but ‘unresurrectable’.